Peningkatan Keterampilan Berhitung Perkalian Siswa Sekolah Dasar Melalui Penggunaan Buku Saku Perkalian pada Kegiatan Bimbingan Belajar KKN di Desa Taman Bali - Ni Komang Ayu Yuliantari; Nurul Isnaini Fitriyana (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service activity aims to improve elementary school students' multiplication skills through the use of the Multiplication Pocket Book in a tutoring program. The activity was implemented using a descriptive qualitative approach and involved 10 elementary school students as mentoring targets. The community service program was conducted over four sessions, each lasting 1 hour and 30 minutes. Data collection techniques were conducted through observation, interviews, and documentation throughout the mentoring process. The results showed a gradual improvement in students' multiplication skills, from understanding basic concepts to mastery of the 1-10 multiplication table. Furthermore, the use of the Multiplication Pocket Book, equipped with a learning achievement initialing system, increased student motivation, self-confidence, and active participation during the tutoring program. Therefore, the Multiplication Pocket Book can be used as a simple and effective learning medium in community service activities to support the improvement of elementary school students' basic arithmetic skills.